2019
DOI: 10.1186/s12957-019-1567-y
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer robotic nipple sparing mastectomy: evaluation of several surgical procedures and learning curve

Abstract: BackgroundFew studies of robotic nipple sparing mastectomy (NSM) were reported. We report feasibility of robotic NSM and determine standard surgical procedure and learning curve threefold.MethodsA cohort of patients with robotic NSM for breast cancer was analyzed. Complications and post-operative hospitalization stay were reported. The same technic was used for all patients except for skin and nipple areolar complex (NAC) dissection. Differences between three surgical procedures of NAC dissection were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 37 publications
(31 reference statements)
2
38
0
Order By: Relevance
“…Mayo reported their results with NSM over the last decade, showing a decrease in complication rate even with the broadening of indications for the procedure to higher‐risk patients; this confirms a team learning curve for the procedure 60 . Interestingly, the robotic approach to NSM, which was only first reported within the last 3 years, already has several published manuscripts regarding the learning curve 44,61‐63 …”
Section: The Learning Curvementioning
confidence: 86%
“…Mayo reported their results with NSM over the last decade, showing a decrease in complication rate even with the broadening of indications for the procedure to higher‐risk patients; this confirms a team learning curve for the procedure 60 . Interestingly, the robotic approach to NSM, which was only first reported within the last 3 years, already has several published manuscripts regarding the learning curve 44,61‐63 …”
Section: The Learning Curvementioning
confidence: 86%
“…Subsequently, few additional publications have described the use of RNSM ( Table 3 ) [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Reported complications include nipple areolar complex necrosis, mastectomy flap necrosis, temporary skin blistering, hematoma, seroma, infection, loss of implant from infection, delayed axillary wound healing, transient brachial plexus neurapraxia (due to arm positioning), transient common peronal nerve neurapraxia (due to patient positioning during surgery).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, future studies assessing the mastectomy skin flap viability may demonstrate low rates of flap complication and thus improved success of immediate breast reconstruction. Although current published number of cases are small, there is a trend for low skin flap necrosis [ 8 , 12 , 16 , 17 , 31 ]. While the same anatomic planes are adhered to during RNSM compared to open, the skin retraction with CO 2 insufflation rather than physical retraction may be less traumatic through the duration of the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 A previous study suggested that the cost of RNSM could be decreased with about 300 procedures, with one robotic surgical system and minimal use of robotic instruments. 17 With those results and the development of cost-effective robotic surgical systems and instruments in this industry, we predict reductions in the cost of RNSM.…”
Section: Pathology and Adjuvant Therapymentioning
confidence: 99%